Unveiling The Dark Side of Transformational Leadership: Examining Leader Dependency and Its Influence on Organizational Dynamics - Andrianto Iskandar (Universitas Pelita Harapan, 2024)
While transformational leadership is often praised for its capacity to inspire change and drive innovation, this paper aims to delve into the less-explored negative repercussions of this leadership style, particularly in terms of fostering excessive leader dependency. The study examines how leader-centric dynamics may compromise team autonomy, stifle creativity, and lead to organizational in efficiencies over time. Through a mixed-method approach involving case studies and survey data from multinational organizations, this research unveils that transformational leader, while empowering, can unintentionally cultivate a reliance on their vision and guidance, thereby constraining the cultivation of self-sustaining leadership within teams. The findings underscore the significance of striking a balance between transformational leadership and autonomy-promoting practices to steer clear of dependency traps. This paper contributes to the expanding body of literature on leadership dynamics by offering a nuanced comprehension of the potential risks associated with transformational leadership. Furthermore, it discusses the implications for leadership development, organizational design, and employee empowerment.